Association of Adverse Perinatal Outcomes of Intrahepatic Cholestasis of Pregnancy With Biochemical Markers: Results of Aggregate and Individual Patient Data Meta-Analyses. Issue 1 (March 2020) - Ovadia, C.; Seed, P.T.; Sklavounos, A.; Geenes, B.; Di Ilio, C.; Chambers, J.; Kohari, K.; Bacq, Y.; Bozkurt, N.; Brun-Furrer, R.; Bull, L.; Estiú, M.C.; et al.
Abstract : ( Lancet . 2019;393:899–909) Intrahepatic cholestasis of pregnancy has been associated with adverse perinatal outcomes, including preterm labor, fetal asphyxia, meconium-stained amniotic fluid, and stillbirth. Although studies have found an increased risk of these complications when the serum bile acid concentration is >40 µmol/L, there currently are no studies to indicate a specific concentration threshold that is predictive of fetal death. The purpose of this systematic review and meta-analysis was to quantify adverse perinatal complications in relation to serum bile acid concentrations and to determine whether specific concentration levels were associated with the risk of stillbirth and preterm birth.